Neuromodulatory effects of transcranial electrical stimulation on emotion regulation in internalizing psychopathologies. (January 2023) - McAleer, Jessica; Stewart, Lindsey; Shepard, Robert; Sheena, Michelle; Stange, Jonathan P; Leow, Alex; Klumpp, Heide; Ajilore, Olusola
Highlights: Offset theta-tACS improves emotion regulation capabilities and depression scores. Sham stimulation appears to have a blunting effect. Verum-first participants show improvement in emotion regulation and clinical scores. Abstract: Objective: We hypothesize offset theta-tACS (transcranial alternating current stimulation) improves emotion regulation (ER) and psychopathology more than transcranial direct current stimulation (tDCS) in participants with internalizing psychopathologies (IPs). Methods: This pilot study utilized a double-blind, pseudo-counterbalanced, sham-controlled design with participants with IPs. Participants were assigned to receive tDCS or tACS, underwent four stimulation sessions (two sham), and completed an emotion regulation task (ERT) during or after stimulation. Participants completed the Beck Depression Inventory before/after the study, the Spielberger State and Trait Anxiety Index after each ERT, and rated their arousal, valence, and perceived reappraisal ability during the ERT. Results: Participants receiving either stimulation type showed a reduction in anxiety, depression, and valence and arousal ratings. We additionally discovered an effect demonstrating those who received sham stimulation first displayed little-to-no change in any score across the study, but tACS participants who received verum stimulation first showed significant improvements in each metric. Conclusions: Improving ER capabilities via theta tACS has the potential to yield beneficial clinical effects. Significance: This study adds validity to the use of non-invasive neuromodulatory methods, especially tACS, to alleviate IPs. Additional research is needed to better understand the effects of sham stimulation. Careful consideration of sham incorporation should be made in future studies.